Prevalence of Coagulase-Negative Staphylococci (CoNS) in Healthy and Sick Cat and Dog Populations in Poland. (March 2022) - Miszczak, M.; Korzeniowska-Kowal, A.; Wzorek, A.; Gamian, A.; Szenborn, L.; Rypuła, K.; Bierowiec, K.
Abstract : Purpose: Coagulase-negative staphylococci (CoNS) constitute a part of the normal microbiota of dogs and cats. These opportunistic bacteria are usually treated as a non-pathogenic or environmental contamination when detected in a sample. Currently, they are gaining the attention of researchers due to reports that they have caused serious infections. The present study reports on the incidence of CoNS colonization in cats and dogs dependent on their state of health. Methods & Materials: The study was conducted between 2019—2021. There were collecting samples from healthy pets (n= 183) and animals with infection of the conjunctiva, upper respiratory tract, or skin (n= 90). Swabs from animals were taken from nares, conjunctival sacs, external auditory canal, oral cavity, the anus, and skin. Isolates of Staphylococcus were classified as CoNS using a coagulase tube test. Species identification was conducted using Matrix Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS). Results: In total, 20 species of coagulase-negative staphylococci were isolated from the examined animals. Around 82.05% (Cl 95% 77.50–86.60%) animals carried any Staphylococcus . A greater number of staphylococci species was observed in cats than in dogs nevertheless the difference was not statistically significant. The most frequently isolated Staphylococcus species were S. felis (44.09%; Cl 95%, 37.80–50.01%), S. epidermidis (43.31%; Cl 95%, 37.01–49.21%), S. warneri (19.13%; Cl 95%, 16.28–21.98%) in cats and S. epidermidis (27%; Cl 95%, 22.19–31.83%), S. saprophyticus (10.29%; Cl 95%, 7.07–13.83%), S. haemolyticus (9.8%; Cl 95%, 7.04–12.81%) in dogs. Conclusion: CoNS are common bacteria in dogs and cats. Depending on the species of animal, some staphylococci more often than others colonize selected anatomical regions in examined pets. The dominant CoNS in domestic animals turned out to be S. felis, S. epidermidis, S. warneri, S. saprophyticus, and S. haemolyticus .